Promoting Multilingualism in the Classroom: A Case Study of ELT Program - Muhammad Nafi Annury (Vision: Journal for Language and Foreign Language Learning, 2017)
The article gives a brief analytical survey of multilingualism practices, its consequences, and its benefits in education and discussions on the appropriate ways towards its achievement in education. Multilingualism refers to speaking more than one language competently. Generally, there are both the official and unofficial multilingualism practices. This study was descriptive qualitative. The subjects of the study were eighty students and divided into two classes. Purposive sampling technique was applied in identifying students who tended to practice multilingualism in education in EFL class. The benefits of multilingualism practices in education were realized by relying on text analysis of the written materials on education and psychology. Personal experience in educational matters especially the educational processes in EFL class is also included. Findings were descriptively presented in continuous prose. Students still had problems on the way they speak and write in English well. However, there were only 1.9% students who felt that they influenced in speaking and even writing English well. It is quite a challenging issue towards students implementing multilingualism within the classroom. Even though, they are already learned English since they were from junior high school, fortunately.